The comparison of anthropometrical parameters of the four-year-old children in the urban and rural Slavonia, Croatia, 1985 and 2005 - Aberle, Neda; Blekić, Mario; Goleš, Ana, liječnica; Pavlović, Ivana, liječnik (2009)
Abstract: The aim of the study is to identify the secular trends in the anthropometrical parameters of the 4-year-old children in Slavonski Brod, Slavonia, Croatia, and the nearby rural area by comparing data of height, weight, and mid-arm circumferences from 2005 with the historical control data published in 1985. The cross-sectional study of 342 children, aged 4 years, from Slavonski Brod and the nearby villages was taken in 2005. The Body height, weight, and mid-arm circumferences were measured and compared with the historical control data from the study performed in 1985 in the same area using the same methods. The data were compared according to sex and the place of residence. Results show that there were no significant differences in the body height, weight, mid-arm circumference and body mass index (BMI) between the urban and rural children in 2005. The Children in 2005 were significantly shorter (103.7 ± 8.3 cm vs. 108.3 cm in 1985, P<0.001, one-sample T test) and had lower weight (17.4 ± 2.7 kg vs. 17.9 kg, P=0.001, one-sample T test) compared with their counterparts in 1985. In 2005 there was no significant difference in the body mass index (kg/m2) between girls and boys in total (15.9 ± 2.12, vs. 16.1 ± 1.8, p=0.262, Independent samples t-test). Differences between the urban and rural parameters have disappeared over the last 20 years, which could be assigned to life-style changes in the rural areas
Bibliografija: 29 jed
Sažetak
Keywords: Antropometrijski parametri -- Djeca -- Grad -- Selo; Slavonija